Estrutura populacional, abundância e distribuição de três espécies do complexo Hoplias aff. malabaricus na planície de inundação do alto rio Paraná, PR/MS. - Santos, Marília Hauser dos (2010)
Hoplias aff. malabaricus presents one of the largest diversities karyotypic inter and intrapopulational, and three species of that complex in the Upper Paraná river floodplain have been identified: two natives (Hoplias sp.2 and Hoplias sp.3) and one introduced (Hoplias sp.1), after the construction of the Itaipu reservoir. This species complex is known by playing a key role in the structuring of the fish assemblages in the plain in subject. In this context, the objective of this dissertation was to determine the population structure, abundance and distribution of those species, with the intention of understanding the processes that guarantee the coexistence of the three species in the ecosystem. For so much, collections were carried, quarterly, from March of 2006 to December of 2007, in nine collection points, belonging to three subsystems (BA, PR, IVI). The results were presented in two chapters. The first chapter aimed to investigate the population structure of the three species of Hoplias, in which higher sexual balance was verified regarding the seasonality and length structure, for Hoplias sp.1, while, that for the native species, higher efficiency was verified in the exploration of the available resources in periods of conspicuous floods. In the second chapter, it was determined the limnologics factors that influenced the abundance and distribution of the species. It was verified, that for Hoplias sp.2, in dry years, the turbidity, total phosphorus and chlorophyll were the most important variables in the determination of her abundance, while in years with intense floods, the flood pulse was the preponderant factor. Similar tendency of distribution was observed between the two native species, which were more abundant in the BA, while Hoplias sp.1 showed higher efficiency in the exploration of altered habitats like PR. These results, besides identify related species different mechanisms to coexist, emphasize the importance of the spatial resources heterogeneity in the population?s dynamics, reinforcing the role of the habitat as structural factor of the same ones, independently, of the phylogenetic relationship.